Micropropagation and Effect of Growth Retardants on Selected Species of Melastomataceae - Poospooragi, Ramani (2005)
This study consists of four parts. The first part was to develop an efficient in vitro micropropagation protocol for Melastoma malabathricum, Melastoma decemfidum, Melastoma dodecandrum and Tibouchina semidecandra. These plants are locally known as 'senduduk'. Nodal segment and shoot tip of each species were used as explants for shoot initiation. Shoot tip was a more suitable explant for M. malabathricum, M. dodecandrum and M. decemfidum shoot initiation performed in full strength Murashige and Skoog (MS) medium supplemented with 30 μM 6-benzylaminopurine (BAP), while nodal explant was chosen for T. semidecandra shoot initiation in full strength MS medium supplemented with 20 μM BAP. Shoot multiplication and elongation was optimal in half strength MS medium supplemented with 6 μM BAP for T. semidecandra, 9 μM BAP for M. malabathricum and 12 μM BAP for M. decemfidum while M. dodecandrum required quarter strength MS medium supplemented with 3 μM BAP. Shoots v cultured on MS medium without any growth regulators supplementation was found to have higher in vitro rooting compared to medium supplemented with naphthalene acetic acid (NAA), indole butyric acid (IBA) and indole acetic acid (IAA). Full strength MS medium was suitable for in vitro rooting of T. semidecandra and M. decemfidum, opposed to half strength MS medium for M. malabathricum and quarter strength MS medium for M. dodecandrum. Rooting in the solid medium was better than liquid medium. A higher percentage of plantlets survived when they were acclimatized for one week compared to plantlets that were directly transferred from tissue culture medium to the soil. The second part of this study was to regenerate shoots directly from the leaf, petiole and internode explants of M. malabathricum. Explants obtained from the most apical part of the plant formed a higher number of shoots compared to those below the apical end. Quarter strength MS medium was the most suitable medium strength for shoot regeneration of all explants tested. The highest number of shoots was formed from the leaf explant at 9 μM BAP, followed by petiole at 6 μM BAP, and internode at 9 μM BAP. The third part of this study was to regenerate shoots from leaf-, petiole- and internode-derived calli of M. malabathricum. A suitable callus induction medium was found to be a full strength MS medium supplemented with 2.5 μM dicamba and 2.5 μM kinetin for leaf explant, 10.0 μM NAA and 2.5 μM BAP for petiole explant, and 10.0 μM NAA and 2.5 μM kinetin for internode explant. Full vi strength MS medium supplemented with 5.0 to 7.5 μM BAP alone had induced multiple shoots from the leaf-derived callus compared to 2.5 to 5.0 μM BAP for petiole-derived callus. A combination of 0.5 μM NAA and 5.0 μM BAP, however, was found to enhance shoot formation from the petiole-derived callus compared to when 5.0 μM BAP was used alone. The final part of this study was to evaluate the effects of growth retardants on vegetative growth and the flowering of M. malabathricum, M. decemfidum and T. semidecandera. Growth retardants (paclobutrazol and flurprimidol) significantly reduced the plant size, induced early flowering and increased the number of flowers formed unlike the untreated plants. Paclobutrazol applied at 200 mg/L (w/v) was found to be suitable for M. malabathricum compared to 300 mg/L (w/v) for M. decemfidum. Flurprimidol applied at 50 mg/L (w/v) concentration was suitable for T. semidecandra.